2017
DOI: 10.1098/rsos.171012
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of fermentation conditions for producing cellulase of Bacillus amyloliquefaciens and its application to goose feed

Abstract: The proper culture conditions for producing cellulase of Bacillus amyloliquefaciens S1, isolated from the cecum of goose was optimized by single-factor experiment combined with orthogonal test. The properties of the cellulase were investigated by DNS method. The appropriate doses of B. amyloliquefaciens S1 were obtained by adding them to goose feed. It indicated that the suitable culture conditions of producing cellulase were the culture temperature of 37°C, the initial pH of 7.0, the incubation time of 72 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 59 publications
3
19
0
3
Order By: Relevance
“…In this study, replacing 5% corn with B.cereus fermented wheat bran did not affect the growth performance of broilers. Suggesting that SSF using xylanase-producing microorganisms can degrade NSP and be used in the pre-treatment of feedstuff, which has similar standpoint to previous studies (Latorre et al, 2015 ; Supriyati et al, 2015 ; Ye et al, 2017 ). Compared with other methods to degrade NSP in diets, such as adding exogenous enzymes (Cardoso et al, 2018 ), appending microbial agents (Wealleans et al, 2017 ), and low temperature freezing (Khadem et al, 2016 ), SSF not only ensures the nutrient level of diets, but optimizes the intestinal microbiota and further improves the digestion and absorption capacity of broiler chickens.…”
Section: Discussionsupporting
confidence: 64%
“…In this study, replacing 5% corn with B.cereus fermented wheat bran did not affect the growth performance of broilers. Suggesting that SSF using xylanase-producing microorganisms can degrade NSP and be used in the pre-treatment of feedstuff, which has similar standpoint to previous studies (Latorre et al, 2015 ; Supriyati et al, 2015 ; Ye et al, 2017 ). Compared with other methods to degrade NSP in diets, such as adding exogenous enzymes (Cardoso et al, 2018 ), appending microbial agents (Wealleans et al, 2017 ), and low temperature freezing (Khadem et al, 2016 ), SSF not only ensures the nutrient level of diets, but optimizes the intestinal microbiota and further improves the digestion and absorption capacity of broiler chickens.…”
Section: Discussionsupporting
confidence: 64%
“…These results are in agreement with other studies performed on cellulase production by Bacillus spp. Optimum temperature for production of cellulase by B. amyloliquefaciens DL-3 49 , Bacillus pumilus EB3 50 and Bacillus amyloliquefaciens 51 was 37 °C. Islam et al 52 reported maximum enzyme production by Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…The cecum of chicken has more diversity of LAB than the small intestine, and LAB isolated from poultry cecum have been reported to have higher enzyme secretion and activity than other probiotics [17,18]. In this study, an Enterococcus strain, L11, was isolated from cecum of a healthy chicken and identified as E. faecium.…”
Section: Introductionmentioning
confidence: 93%